(untitled) (London, 1998)
The keeping of ornamental fishes is the biggest animal related hobby in the world. Many textbooks and most of the related literature focus on diseases of fish designated for human consumption, especially aquaculture species. This Self-Assessment Colour Review provides the reader with over 250 clinical cases and covers all of the important medical and surgical conditions found in ornamental fishes. The well illustrated cases appear randomly and are targeted at different levels of expertise. In addition, questions pertaining to fish anatomy, physiology, husbandry, and identification have been included to make this text both educational and comprehensive. A team of internationally known and respected authors have written the questions and detailed explanatory answers, and Dr Lewbart has edited the text so that it is practical, informative and easy to read. Veterinary practitioners, professional aquarists, hobbyists, and students will find this book to be a valuable addition to their education and clinical training.
Keywords: Ornamental fishes,Ornamental fishes,Cá cảnh,Cá cảnh; Diseases,Diseases,Problems, exercises, etc.,Bệnh,Bệnh,Câu hỏi và bài tập